2019
DOI: 10.21203/rs.2.18793/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NLRP3 maintains healthy pericytes in the brain

Abstract: Background Pericytes regulate structure and function of cerebral capillaries. Growing evidence shows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…We acknowledge support by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) and Saarland University within the funding programme Open Access Publishing. The older version of this manuscript has been released as a pre-print at Research Square (Quan et al, 2019 ).…”
mentioning
confidence: 99%
“…We acknowledge support by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) and Saarland University within the funding programme Open Access Publishing. The older version of this manuscript has been released as a pre-print at Research Square (Quan et al, 2019 ).…”
mentioning
confidence: 99%
“…To this end, we conducted the pabinafusp alfa uptake assays utilizing human immortalized astrocyte and pericytes model cells, HASTR/ci35 and HBPC/ci37 cells. These cell lines were selected because we and other researchers have shown that they retain many of their original characteristics (Furihata et al, 2016;Kitamura et al, 2018;Umehara et al, 2018;Quan et al, 2020;Das et al, 2022).…”
Section: Characterization Of Pabinafusp Alfa Uptake By Human Astrocyt...mentioning
confidence: 99%